A, ANALISIS AGROINDUSTRI DODOL BUAH-BUAHAN DI DESA BUANTAN BESAR KECAMATAN SIAK KABUPATEN SIAK (STUDI KASUS UD. PUTRA MANDIRI) - darus darus; Ridho Ilahi (Jurnal Agribisnis, 2020)
Agroindustry is a form of industrial business which has the main raw materials of agricultural products which can increase added value, one of which is the raw material in the form of fruit which is processed into fruit lunkhead. The problem generally faced by entrepreneurs is the instability of raw material availability. This study aims to analyze (1) the characteristics of entrepreneurs, workers and business profiles (2) Use of raw materials and supporting materials, production technology, processing and production stages (3) Production costs, income, efficiency and added value. This research uses a case study method at UD. Putra Mandiri in Buantan Besar Village, Siak District, Siak Regency. Sampling was done by census. The number of respondents taken was 7 people consisting of 1 entrepreneur and 6 workers. Types of data consist of primary and secondary data. The data analysis method consisted of qualitative and quantitative descriptive analysis. The results showed that: (1) The age of the entrepreneur is 51 years. 14 years of entrepreneurial education. Total family dependents of 4 people and 20 years of business experience. The average labor age is 31.5 years. The average educational level of the workforce is 10.5 years. The number of family dependents for the workforce is 1.6 people on average. The business was founded in 2000 with its own source of capital and a workforce of 6 people (TKLK). (2) The raw material used is 120 kg / production process. The resulting production is 240 Kg / Production Process. (3) The total cost of the dodol fruit agro-industry is Rp. 5,103,828 / Production process. Gross income of Rp. 12,000,000 / Production process and net income of Rp. 6,896,172 / Production Process. An efficiency of 2.3 is efficient. The added value obtained is Rp. 3,826,000 / Kg. Value added ratio of IDR 3,826%. Profit margin Rp. 62,000 / Kg. The ratio of other input contributions was 6,270% and entrepreneur's profit was 6,169%.